Models of Variability and Circadian Rhythm in Heart Rate, Blood Pressure, and QT Interval for Healthy Subjects Who Received Placebo in Phase I Trials - Minocha, Mukul; Li, Hong; Chiu, Yi‐Lin; Carter, David; Othman, Ahmed A. (Clinical and translational science, 2019)
This work characterized the time‐course, circadian rhythm, and inherent variability in key cardiovascular variables (heart rate, corrected QT interval, and systolic and diastolic blood pressure) that are routinely collected as part of safety monitoring in phase I trials. Longitudinal data from 1,035 healthy volunteers who received placebo in 65 single‐dose and multiple‐dose phase I trials conducted by AbbVie were compiled and analyzed using nonlinear mixed‐effects modeling. An independent nonlinear mixed‐effects model was developed for each variable, and combinations of cosine functions were used to capture circadian oscillations. Gender, race, age, and body weight were significant covariates for variability in baseline measures, and the contributions of these covariates were quantitatively characterized. Based on the extensive data set analyzed, the developed models represent valuable tools to help contextualize and differentiate inherent variability that can be expected in a typical phase I setting from true drug‐related cardiovascular safety signals. In addition, these placebo models can be used to support exposure–response analyses that estimate treatment‐related effects on the evaluated cardiovascular measures.